Preparation method and application of carbon-supported high-entropy intermetallic compound catalyst

The preparation of carbon-laden high entropy intermetallic compound catalysts by in-situ carbon-thermal reduction method solves the problems of high platinum dosage and complex preparation methods in the prior art, and achieves efficient and simple catalyst preparation and excellent electrocatalytic performance.

CN119800417APending Publication Date: 2025-04-11ANHUI SCI & TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311298607.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the amount of platinum in the proton exchange membrane fuel cell catalyst, and the preparation method of high-entropy intermetallic compound catalyst is complex, the preparation efficiency is low, and it is difficult to achieve industrial application.

Method used

By using in situ carbon thermal reduction method, a high entropy intermetallic compound catalyst with 3 to 5 nm carbon was prepared by immersing the platinum salt and five non-precious metal salts on a carbon material support, ultrasonic mixing and freeze-drying, and then high-temperature quenching treatment in the H2/Ar environment.

Benefits of technology

The preparation of high-entropy intermetallic compound catalysts without specific equipment is achieved, with simple methods and easy industrialization. The catalysts exhibit good electrocatalytic performance in oxygen reduction and hydrogen evolution reactions, surpassing the performance of commercial catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800417A_ABST
    Figure CN119800417A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a carbon-supported high-entropy intermetallic compound catalyst, and belongs to the field of new energy materials. The method comprises the following steps: (1) carrying out acid treatment on carbon powder; (2) adding the carbon powder treated in the step (1), chloroplatinic acid and a non-noble metal salt solution into a glass sample bottle, ultrasonically mixing uniformly, and then freeze-drying; and (3) carrying out high-temperature quenching on the product obtained in the step (2) in an N2 environment at 900-1000 DEG C to obtain the high-entropy intermetallic compound catalyst. The high-entropy intermetallic compound catalyst prepared by the preparation method disclosed by the invention shows good catalytic performance when being used as a fuel cell cathode oxygen reduction or water electrolysis hydrogen evolution catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy materials, and specifically relates to a method for preparing a carbon-supported high-entropy intermetallic compound catalyst and its application in proton exchange membrane fuel cells and water electrolysis hydrogen production technology. Background Art

[0002] Proton exchange membrane water electrolysis (PEMWE) can be well coupled with new energy sources such as wind energy and solar energy to reduce the cost of hydrogen production and develop a hydrogen energy economy. Compared with alkaline water electrolysis (AME), PEMWE has the advantages of low cell corrosion, high electrolysis efficiency, compact device structure, and high hydrogen production purity. However, the disadvantages of PEMWE are high cost and high price. At present, since the catalyst is a platinum group precious metal, its commercialization process is seriously restricted. Preparing a high-activity low-Pt content catalyst is a common method to reduce the amount of Pt used.

[0003] The method to reduce the Pt content is usually to form a PtM alloy with a non-precious metal M. However, under actual working conditions, M will precipitate and the activity will continue to decrease. Recently, Pt-based high-entropy intermetallics (HEIs) composed of at least five elements have become a research hotspot. They have both diversified atomic composition and long-range ordered atomic arrangement of traditional intermetallic compounds. It has the following advantages: ① Multi-metals not only reduce the amount of Pt, but also the synergistic effect between metals and the ordered site spacing effect can lead to fine-tuning of the electronic structure and optimize its electrocatalytic HER activity. ② In terms of thermodynamics, the multi-composition can form a high entropy effect, the structure is more stable, and the corrosion resistance is enhanced.

[0004] Elements at different positions in the periodic table have different properties and are immiscible, so how to achieve the mixing of multiple elements in ultra-small nanoparticles to form high-entropy materials remains a very big challenge. At present, high-entropy materials are usually synthesized by high-temperature rapid thermal shock synthesis, which requires unique Joule heating equipment and the amount of catalyst prepared is limited. Moreover, this rapid heating and rapid cooling is not conducive to the formation of small-sized ordered structures of high-entropy intermetallic compounds. Therefore, finding a simple, efficient and universal method to form nanoscale ordered high-entropy intermetallic compound particles has certain promotion significance for the industrial application of ordered high-entropy intermetallic compound nanomaterials. Summary of the invention

[0005] In order to overcome the deficiencies and shortcomings of the prior art, the present invention aims to provide a method for preparing a carbon-supported high entropy intermetallic compound catalyst and its application. The raw materials for preparing the carbon-supported high entropy intermetallic compound catalyst in this method are commercial reagents, which are convenient and easy to obtain and inexpensive.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A method for preparing a carbon-supported high-entropy intermetallic compound catalyst and its application, comprising the following steps: (1) Mix 2 mol / L hydrochloric acid with carbon powder and reflux at 100-140°C for 3-10 hours. Filter and wash the refluxed sample, and place the filter cake in a forced air drying oven and dry it at 60°C for 24 hours.

[0008] (2) mixing chloroplatinic acid, non-precious metal salt, and acid-treated carbon material, performing ultrasonic mixing to uniformly mix, and then freeze-drying; (3) The product obtained in step (2) is quenched at 600-800° C. in a H2 / Ar environment to obtain fuel cell and water electrolysis catalysts Pt3M / C and PtM / C, wherein M is composed of equimolar five-element non-precious metals.

[0009] Preferably, the non-precious metal salt is five of Fe salt, In salt, Cu salt, Co salt, Cr salt, Mn salt and Ni salt.

[0010] Preferably, the non-precious metal salt is any five of the seven selected from ferric chloride, indium nitrate, copper chloride, cobalt chloride, chromium chloride, manganese chloride and nickel chloride.

[0011] Preferably, the carbon material is carbon powder (BP2000) or carbon powder (EC600JD).

[0012] Preferably, the molar ratio of chloroplatinic acid to the non-precious metal salt is 3:1 or 1:1.

[0013] Preferably, the mass ratio of the high entropy intermetallic compound to the carbon powder is 10%-60%.

[0014] Preferably, the freeze drying is pre-freezing followed by vacuum drying. The freeze drying method can keep the Pt4+ and non-precious metal ion precursors uniformly dispersed in the carbon material.

[0015] Preferably, the pre-freezing temperature is -35 to -45°C for 3 to 8 hours, and more preferably, the pre-freezing temperature is -40°C for 6 hours.

[0016] Preferably, the vacuum drying temperature is room temperature.

[0017] Preferably, the vacuum drying time is 24-48 hours.

[0018] Preferably, the high temperature quenching treatment time is 12-24 hours, and a carbon-supported 3-5 nm high entropy intermetallic compound catalyst is obtained by controlling the high temperature quenching treatment time and temperature.

[0019] The Pt3M / C and PtM / C high entropy metal compounds prepared by the method described above are used as electrode catalysts in fuel cells and water electrolysis.

[0020] The present invention adopts an in-situ carbon thermal reduction method. First, platinum salt and five non-precious metal salts are impregnated on a carbon material carrier. After ultrasonic uniform dispersion, multiple metal precursors are uniformly adsorbed on the carbon carrier by freeze drying in the process of removing water. In the subsequent heat treatment, the carbon carrier has reducing properties at high temperatures, and the metal precursors are reduced in situ to form high-entropy metal compounds with small particle size and highly ordered structure. This method does not require hydrogen reduction, overcomes the danger and strong reducing properties of hydrogen reduction at high temperatures, and inhibits the strong reducing properties that cause particles to easily agglomerate and grow. The obtained material can be used as an electrode material in fuel cells and water electrolysis.

[0021] Compared with the prior art, the present invention has the following advantages and effects: The present invention provides a preparation method of a carbon-supported high-entropy intermetallic compound catalyst and its application, which has the advantages of no need for specific equipment, simple method, easy industrialization, etc. The prepared high-entropy intermetallic compound material exhibits good electrocatalytic performance in oxygen reduction reaction and hydrogen evolution reaction performance tests. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD pattern of ordered Pt(Fe0.2In0.2Mn0.2Cr0.2Cu0.2) / C prepared in Example 4.

[0023] Figure 2 TEM image of ordered Pt(Fe0.2In0.2Mn0.2Cr0.2Cu0.2) / C prepared in Example 4.

[0024] Figure 3 This is the oxygen reduction performance curve of the ordered Pt(Fe0.2In0.2Mn0.2Cr0.2Cu0.2) / C prepared in Example 4.

[0025] Figure 4 This is a hydrogen evolution performance curve of the ordered Pt(Fe0.2In0.2Mn0.2Cr0.2Cu0.2) / C prepared in Example 4. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with examples, but the examples are only preferred embodiments of the present invention and are not intended to limit the present invention.

[0027] Example 1 Weigh 5g of carbon powder (BP2000 or EC600JD) into a round-bottom flask, add 2mol / L hydrochloric acid and stir magnetically for 30 minutes. After stirring and dispersing, reflux in a 120℃ oil bath for 8 hours. Filter and wash the refluxed product, wash the filter cake with water and ethanol three times, and dry it in a 60oC forced air drying oven for 24 hours.

[0028] Example 2 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, indium nitrate, copper chloride, cobalt chloride and chromium chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, copper, cobalt and chromium was controlled to be 5:1:1:1:1:1, that is, the atomic ratio of noble metal to non-noble metal was 1:1, and the mass ratio of metal atoms to carbon powder was 1:4. Then, it was freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 900℃ and a time of 48h to obtain the product fuel cell electrode active material Pt(Fe0.2In0.2Cu0.2Co0.2Cr0.2) / C.

[0029] Example 3 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, indium nitrate, copper chloride, cobalt chloride and chromium chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, copper, cobalt and chromium was controlled to be 15:1:1:1:1:1, that is, the atomic ratio of noble metal to non-noble metal was 3:1, and the mass ratio of metal atoms to carbon powder was 1:4. Then, it was freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 900℃ and a time of 48h to obtain the product fuel cell electrode active material Pt3(Fe0.2In0.2Cu0.2Co0.2Cr0.2) / C.

[0030] Example 4 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, indium nitrate, manganese chloride, chromium chloride and cupric chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, manganese, chromium and copper was controlled to be 5:1:1:1:1:1, that is, the atomic ratio of noble metal to non-noble metal was 1:1, and the mass ratio of metal atoms to carbon powder was 1:9. Then, freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 900℃ and a time of 48h to obtain the product fuel cell electrode active material Pt(Fe0.2In0.2Mn0.2Cr0.2Cu0.2) / C.

[0031] Example 5 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, indium nitrate, manganese chloride, chromium chloride and cupric chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, manganese, chromium and copper was controlled to be 5:1:1:1:1:1, that is, the atomic ratio of noble metal to non-noble metal was 1:1, and the mass ratio of metal atoms to carbon powder was 1:4. Then, it was freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 900℃ and a time of 48h to obtain the product fuel cell electrode active material Pt(Fe0.2In0.2Mn0.2Cr0.2Cu0.2) / C.

[0032] Example 6 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, indium nitrate, manganese chloride, chromium chloride and cupric chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, manganese, chromium and copper was controlled to be 15:1:1:1:1:1, that is, the atomic ratio of noble metal to non-noble metal was 3:1, and the mass ratio of metal atoms to carbon powder was 1:9. Then, freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 1000℃ and a time of 12h to obtain the product fuel cell electrode active material Pt3(Fe0.2In0.2Mn0.2Cr0.2Cu0.2) / C.

[0033] Example 7 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, manganese chloride, chromium chloride, copper chloride and cobalt chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, manganese, chromium and copper was controlled to be 5:1:1:1:1:1, that is, the atomic ratio of noble metal to non-noble metal was 1:1, and the mass ratio of metal atoms to carbon powder was 1:4. Then, it was freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 1000℃ and a time of 12h to obtain the product fuel cell electrode active material Pt(Fe0.2Mn0.2Cr0.2Cu0.2Co0.2) / C.

[0034] Example 8 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, manganese chloride, chromium chloride, copper chloride and cobalt chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, manganese, chromium and copper was controlled to be 5:1:1:1:1:1, that is, the atomic ratio of noble metal to non-noble metal was 1:1, and the mass ratio of metal atoms to carbon powder was 3:2. Then, freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 1000℃ and a time of 12h to obtain the product fuel cell electrode active material Pt(Fe0.2Mn0.2Cr0.2Cu0.2Co0.2) / C.

[0035] Example 9 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, cobalt chloride, manganese chloride, chromium chloride and cupric chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, manganese, chromium and copper was controlled to be 5:1:1:1:1:1, that is, the atomic ratio of noble metal to non-noble metal was 1:1, and the mass ratio of metal atoms to carbon powder was 1:4. Then, it was freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 1000℃ and a time of 12h to obtain the product fuel cell electrode active material Pt(Fe0.2In0.2Mn0.2Cr0.2Co0.2) / C.

[0036] Example 10 First, the acid-treated carbon powder was added to a glass sample bottle, and then chloroplatinic acid, ferric chloride, indium nitrate, manganese chloride, chromium chloride and nickel chloride solutions were added. The carbon powder was dispersed and mixed evenly with the solution by ultrasound. The atomic ratio of platinum, iron, indium, manganese, chromium and copper was controlled to be 5:1:1:1:1:1, that is, the atomic ratio of precious metals to non-precious metals was 1:1, and the mass ratio of metal atoms to carbon powder was 1:4. Then, it was freeze-dried, first pre-frozen at -40 oC for 6h, and then vacuum dried for 24h. The obtained product was quenched at high temperature in a N2 environment, with a calcination temperature of 1000℃ and a time of 12h to obtain the product fuel cell electrode active material Pt(Fe0.2In0.2Mn0.2Cr0.2Ni0.2) / C.

[0037] Performance Test: (1) Phase characterization was performed using an X-ray diffractometer, with the test voltage set to 35 kV and the current set to 30 mA. The XRD pattern of the carbon-supported platinum-based intermetallic compound prepared in Example 4 is shown in the attached figure. Figure 1 The diffraction peaks of the prepared carbon-supported platinum-based intermetallic compounds are consistent with the PDF standard card, indicating that the ordered carbon-supported platinum-based intermetallic compounds have been successfully prepared. The grain size calculated by the Scherrer formula is about 4 nm.

[0038] (2) The morphology was characterized using a JEM-2100F transmission electron microscope with a test voltage of 200 kV. The TEM image of the carbon-supported platinum-based intermetallic compound prepared in Example 4 is shown in the attached figure. Figure 2 The prepared carbon-supported platinum-based intermetallic compound has uniform particle distribution and a particle size of 3 to 5 nm, indicating that a carbon-supported platinum-based intermetallic compound with small-sized particles and uniform dispersion has been successfully prepared;

[0039] (3) The electrocatalytic performance was characterized in a 0.5 mol / L H2SO4 solution using a three-electrode system. High-purity hydrogen was introduced for half an hour before the test to saturate the hydrogen content in the electrolyte. Weigh 5 mg of carbon-supported intermetallic compound powder, add 50 μL of Nafion (5%) solution and 950 μL of ethanol mixed solution with a pipette, and after ultrasonic dispersion, use a pipette to transfer 5 μL of the slurry and drop it on the surface of the L-shaped glassy carbon electrode. The catalyst loading on the electrode was 0.128 mg / cm2, and the hydrogen evolution polarization curve was obtained at a scanning rate of 5 mV / s. The electrocatalytic hydrogen evolution polarization curve of the carbon-supported platinum-based intermetallic compound prepared in Example 4 is shown in the attached figure. Figure 3 The prepared Pt(Fe0.2In0.2Mn0.2Cr0.2Cu0.2) / C has a lower overpotential for electrocatalytic hydrogen evolution than the commercial Pt / C catalyst, indicating that the prepared carbon-supported high-entropy platinum-based intermetallic compound has an electrocatalytic hydrogen evolution activity that exceeds that of commercial catalysts in an acidic environment, showing excellent catalytic efficiency for water electrolysis.

[0040] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon-supported high entropy intermetallic compound catalyst and its application, comprising the following steps: (1) Reflux treatment of carbon powder with hydrochloric acid; (2) adding the carbon powder, chloroplatinic acid and a non-precious metal salt solution containing Fe, In, Cu, Co, Cr, Mn and Ni treated in step (1) into a glass sample bottle, followed by ultrasonic treatment, and freeze-drying the sample after ultrasonic dispersion; (3) quenching the powder product obtained in step (2) at 900-1000° C. in an inert atmosphere to obtain a carbon-supported high-entropy intermetallic compound catalyst.

2. The method according to claim 1, characterized in that The carbon powder is one of Cabot BP-2000 carbon powder and EC600JD. The method of acid-treating carbon powder is to mix 2 mol / L hydrochloric acid with carbon powder and reflux for 3-10 hours at 100-140°C. The sample after reflux is filtered and washed, and the filter cake is placed in a blast drying oven and dried at 60°C for 24 hours.

3. The method according to claim 1, characterized in that The non-precious metal salts mixed with carbon powder and chloroplatinic acid are any five of the seven kinds of ferric chloride, indium nitrate, copper chloride, cobalt chloride, chromium chloride, manganese chloride and nickel chloride.

4. The method according to claim 2, characterized in that: The molar ratio of the chloroplatinic acid and the non-noble metal salt is 3:1 or 1:

1.

5. The method according to claim 2, characterized in that: The mass ratio of the high entropy intermetallic compound to the carbon powder is 10%-60%.

6. The method according to claim 2, characterized in that The freeze drying is performed by pre-freezing in a vacuum dryer and then vacuum drying.

7. The method according to claim 2, characterized in that The pre-freezing temperature is -35°C-45°C, and the pre-freezing time is 3-8h.

8. The method according to claim 2, characterized in that: The vacuum drying time is 24h-48h.

9. The method according to claim 3, characterized in that: The inert atmosphere environment is high-purity nitrogen or argon; the high-temperature quenching time is 12-24h.

10. Use of the high entropy intermetallic compound catalyst prepared by the method according to any one of claims 1 to 9 in oxygen reduction reaction and hydrogen evolution reaction.